Rare primary choroidal melanoma in a dog, with optic nerve infiltration - Porfirio, Geórgia Bajer Fernandes de Freitas; Mello, Elaine Souza; Brunato, Carinne Liesse; Perlmann, Eduardo (Brazilian Journal of Veterinary Research and Animal Science, 2022)
Intraocular melanocytic neoplasms are common in dogs. However, the choroidal location of these neoplasms and their infiltration into the optic nerve are unusual. This paper reports a case of primary choroidal melanoma in a 12-year-old male Dachshund. On the first examination, the animal presented left eye blepharospasm, protrusion of the nictitating membrane, conjunctival hyperemia, moderate congestion, hyphema, and intraocular hypertension. Opacity hindered the performance of fundoscopy in the affected eye. The ocular ultrasound examination revealed a cupuliform mass in the choroid. Due to suspected intraocular neoplasia, an exenteration was performed. Histopathological examination revealed primary choroidal melanoma with scleral and optic nerve invasion.